Widespread volcanism in the Greenland–North Atlantic region explained by the Iceland plume. Issue 1 (January 2019) - Steinberger, Bernhard; Bredow, Eva; Lebedev, Sergei; Schaeffer, Andrew; Torsvik, Trond
Abstract In the classical concept, a hotspot track is a line of volcanics formed as a plate moves over a stationary mantle plume. Defying this concept, intraplate volcanism in Greenland and the North Atlantic region occurred simultaneously over a wide area, particularly around 60 million years ago, showing no resemblance to a hotspot track. Here, we show that most of this volcanism can nonetheless be explained solely by the Iceland plume interacting with seafloor spreading ridges, global mantle flow and a lithosphere (the outermost rigid layer of the Earth) with strongly variable thickness. An east–west corridor of thinned lithosphere across central Greenland, as inferred from new, highly resolved tomographic images, could have formed as Greenland moved westward over the Iceland plume between 90 and 60 million years ago. Our numerical geodynamic model demonstrates how plume material may have accumulated in this corridor and in areas east and west of Greenland. Simultaneous plume-related volcanic activities starting about 62 million years ago on either side of Greenland could occur where and when the lithosphere was thin enough due to continental rifting and seafloor spreading, possibly long after the plume reached the base of the lithosphere. Volcanism across the North Atlantic region 62 million years ago is consistent with an Iceland plume source, despite the absence of a classic hotspot track, suggest tomographic images and geodynamic models.